A metáfora conceptual na construção do discurso jornalístico - Silva, Luciana Soares da (2008)
This work seeks to identify and to engage in a critical approach on the uses of metaphors in the journalistic discourse. Such goals were motivated by the critical observation of newspapers in which we found the recurrence of metaphors in the making news; therefore debunking traditional view that recognizes metaphors only in literary texts. In order to achieve our purpose, we selected texts from the mainstrain newspaper Folha de S. Paulo´s coverage of Brazilian presidential election in the period between September and October 2006, as the corpus of this research. Then, we proceeded with the analysis, mainly based on the teorethical approach of the Discourse Analysis and Cognitive Linguistic studies. While the former teach us that 'language' is associated with historical and social processes and therefore cannot be separated from the society that produces it, by introducing the category 'conceptual metaphor', the later provides a understanding of metaphor as a cognitive and social phenomenon. In this research, we have found that metaphors create the journalistic discourse as a linguistic-discursive strategy that both enables the construction of a particular discourse in the assessment and consumption of news, and produces effects over the meanings of news coverage. Moreover, taking the case studies here analyzed, we maintain that the metaphors create a web of meanings over the presidential election, which depict candidates´s images in a particular way; influencing, therefore, the reader's opinion